1999
DOI: 10.1021/ma981579c
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Conversion of Hydroxy-Containing Imides to Benzoxazoles:  Polymer and Model Compound Study

Abstract: A series of hydroxy-containing polyimides, containing pendent hydroxyl groups ortho to the heterocyclic imide nitrogen, were prepared via the solution condensation of aromatic dianhydrides with bisaminophenols. The polyimides were found to undergo thermal conversion to polybenzoxazoles upon heating between 350 and 500 °C under nitrogen or vacuum. The thermal conversion was accompanied by loss of carbon dioxide. No other volatile byproducts were detected by IR or NMR. Structures were confirmed by IR, solid-stat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
97
0

Year Published

2000
2000
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 133 publications
(106 citation statements)
references
References 16 publications
9
97
0
Order By: Relevance
“…At 550°C, PBO (IV) was prepared by the thermal conversion of PI (II) via the PBO precursor (III). 19,20 Characterization Elemental analyses were performed by the Analytical Laboratory of the Korea Institute of Chemical Technology; see Table I. The values in parentheses are those calculated for the chemical formulas.…”
Section: Film Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…At 550°C, PBO (IV) was prepared by the thermal conversion of PI (II) via the PBO precursor (III). 19,20 Characterization Elemental analyses were performed by the Analytical Laboratory of the Korea Institute of Chemical Technology; see Table I. The values in parentheses are those calculated for the chemical formulas.…”
Section: Film Preparationmentioning
confidence: 99%
“…Mathias et al 19,20 reported that a series of hydroxy-containing PIs, containing pendant hydroxyl groups ortho to the heterocyclic imide nitrogen, were prepared by solution condensation of aromatic dianhydrides with bisaminophenols. PBOs were synthesized from PIs with a carboxy-benzoxazole intermediate.…”
Section: Introductionmentioning
confidence: 99%
“…Aromatic PAIs possess balanced characteristics between polyamides and polyimides such as high thermal stability and good mechanical properties together with ease of processability (Imai, 1996). Besides, Mathias and others reported the possible thermal conversion of orthohydroxypolyimides into PBOs with loss of carbon dioxide at temperature around 400°C (Tullos et al, 1999;Park et al, 2007). The above features inspired the idea to incorporate amide and imide groups into one benzoxazine compound, which can be developed as a precursor for PBOs with better processability.…”
Section: Introductionmentioning
confidence: 99%
“…The generally accepted mechanism for the imide-to-polybenzoxazole thermal rearrangement involves the decarboxylation of the ortho-hydroxypolyimide at very high temperature (well over 350 °C) through the previous formation of a carboxybenzoxazole, with further elimination of a CO2 molecule [24]. Additionally, other functionalized polyimides have been studied as precursors, particularly polyimides containing ortho-ester groups [25].…”
Section: Introductionmentioning
confidence: 99%